Hiperimagem: a imagem em hipermídia aplicada no conhecimento científico - imagem e conhecimento científico - Messa, Éric Eroi (2007)
This research proposes to identify, in hypermedia works, small units of the work, called hyperimages, which are composed by verbal and non-verbal resources, capable of participate in the process of creation of knowledge in an active way. A large part of the knowledge areas is influenced by prioritizing the verbal matrix applied in print media. In these cases it is common to see an image simply as an illustration of the text it accompanies, being a redundant element in the process of production of knowledge. In the case of a relationship between image and text, the non illustrative image is one where the level of redundancy is small; that is to say, it supplies additional information to what is in the text. In the case of hypermedia works, the language itself offers a mixture of verbal, sound and visual matrices. This work deals with the hypothesis that this mixture of hypermedia language and the possibilities offered by other programming resources can provide the creation of hyperimages. These act by taking advantage of the resources of each matrix in order to generate a sensitive expression, promoting stimuli during the process of perception, and creating questions which collaborate toward an active construction of knowledge. The potential of image applied in hypermedia offers subsidies that allow the reflection on the alternative models of knowledge production. Reticularity, non-linearity and editing, are some of the characteristics which support these alternative models. The integration of a hyperimage in the inside of a network of hyperimages expands the normal ways of understanding, taking them much further than an illustrative participation of the image. The methdology was applied in order to establish a relationship between the areas of communication and hypermedia. So, we analyzed hypermedia works resulting from scientific research and, therefore, used a technical base using three options. First, valuing the sensitive/aesthetic aspect based on the work of philosopher Hans-Georg Gadamer. Secondly, a conceptual option based on Pierce's firstness, present in the theory of signs. Third, Marshall McLuhan's notion of multi sensibilities as a concept which dialogs with the presence of hyperimages in hypermedia environments